Peran Filsafat Stoisisme dalam Fenomena Kesehatan Mental Perspektif Psikologi dan Islam - Yas Hadi Maulana; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study is to discuss the role of stoicism in overcoming mental health phenomena from the perspective of psychology and the Islamic religion. This research is a qualitative research carried out by analyzing various stoic philosophical literature. The object of this research is stress (daily hassles and personal stressors). The analysis technique uses the description method, namely providing a clear explanation accompanied by literature about the text or manuscript. Description discusses concepts and ideas. Data interpretation uses the content analysis method, this method is used to view documents or manuscripts. The results and discussion of stress can be avoided by applying a control dichotomy, namely the S-T-A-R-S (Stop, Think and Assess, Respond) mindset and its function in dealing with adversity and calamity, controlling personal interpretation and perception, strengthening mentality.